Combining default choices and an encounter decision aid to improve tobacco cessation in primary care patients: protocol for a cluster-randomized trial - Christina Hempel-Bruder; Inès Habfast-Robertson; Marie-Anne Durand; Ivan Berlin; Joachim Marti; Yasser Khazaal; Carlos Quinto; Mohamed Faouzi; Kevin Selby (BMC Primary Care, 2022)
Abstract Background While quitting smoking dramatically decreases overall mortality, general practitioners (GPs) are less likely to prescribe medications for smoking cessation than other cardiovascular risk factors. Guidelines recommend providers first assess patients’ “readiness” to quit, an “opt-in” strategy, but only a minority of tobacco users are ready to quit on a given day. An “opt-out” strategy offering treatment as the default choice increased quit attempts in hospital and with pregnant women, but has not been tested in primary care. We will assess the efficacy of training GPs to offer treatment as the default choice using an encounter decision aid with current smokers seen in primary care. Methods This is a pragmatic cluster-randomized controlled superiority trial with block randomization at the GP level in private practice in French-speaking Switzerland. GPs will be blinded to the arm allocation. The intervention is a half-day training course teaching an ‘opt-out’ approach to smoking cessation using an encounter decision aid (paper or electronic). GPs in the enhanced usual care group receives a brief refresher training about smoking cessation without changing their behaviour. GPs in both arms will recruit 23 patients each prior to routine primary care visits. The primary outcome is the effect of consulting a GP who received the intervention on the 7-day, point prevalence, smoking abstinence 6 months after the baseline appointment. Secondary outcomes include continuous abstinence; number of quit attempts; use of smoking cessation aids; patient-perceived involvement in discussions; and changes in GP behaviour. Patient outcomes will be collected using paper and telephone questionnaires. Assuming 15% drop-out, recruiting 46 GPs with 23 patients each will give us 80% power to detect an increase in smoking cessation from 4% (control) to 10.5% (intervention), with an alpha < 0.05. Discussion GP visits are an opportunity to administer proven smoking cessation treatments. We hypothesize GPs offering smoking cessation treatment as the default choice using an encounter decision aid will increase the number of patients who quit. This study could significantly change our approach to smoking cessation in primary care. Default choices and the electronic decision aid are low-cost, easily diffusible interventions. Trial registration ClinicalTrials.gov Identifier: NCT04868474, First Posted May 3, 2021, Last Update Posted October 6, 2021.